PEMBUATAN KERTAS DAUR ULANG DARI LIMBAH SERAT KELAPA MUDA DAN KERTAS BEKAS SEBAGAI ALTERNATIF KERTAS SENI UNTUK INDUSTRI - Enda Apriani; Heni Dwi Kurniasari (PROSIDING SNAST, 2018)
Paper is one of the products produced from the processing of wood fiber, and non-wood plants, as well as secondary fibers derived from waste paper. These plant fibers are natural fiber materials from agricultural waste. The remaining processing of agricultural products in abundance around our environment, such as young coconut fiber can be used as recycled paper. Processing of waste paper into recycled products has been carried out. One of them is to make young coconut fiber into recycled paper for industry. This research was conducted with the aim to determine the composition of raw materials and variations of the optimal type of adhesive to the tensile strength and tear resistance of paper from young coconut fiber waste and HVS type used paper by using PVAc type adhesive. This study uses NaOH as a pre-treatment that functions in the separation and decomposition of cellulose fibers and noncellulose and makes young coconut fibers stronger. The research variable used is the composition of young coconut fiber (SKM) raw materials and used paper (KB) of 25: 75; 50: 50; 75: 25 (%) on variations in the proportion of PVAc adhesive types, namely 2% and 5% respectively.The results of this study were obtained with the most optimal composition in producing art paper for industrial needs, namely on the composition of raw materials SKM: KB (75: 25) on a variation of 2% PVAc adhesive, with the average value of the most attractive tensile strength of 7, 23 N / m on average gram 192.92 g / m² and the average tear index is 2.76 mN m² / g.